KEBIJAKAN HUKUM PIDANA PERTANGGUNGJAWABAN KORPORASI TERHADAP TINDAK PIDANA PERBANKAN DALAM SISTEM HUKUM DI INDONESIA - Bambang Purwogandi Dito Ari Legowo; Sri Endah Wahyuningsih (Jurnal Hukum Khaira Ummah, 2019)
Based on the results of this study it is known that all court decisions fully adhere to the principle of legality in the application of legal subjects and offenses under the Banking Act listed in Article 46 s.d. 50 A, which no one applies corporate crime. In addition, there is the application of the Special Law, namely the Law of the Republic of Indonesia Number 20 Year 2001 on the Amendment of Law Number 31 Year 1999 on the Eradication of Corruption, for banking crimes which contain elements of state losses. Banking Act is more oriented on the offender (person), not yet seen victim-oriented criminal type so it should also be considered the existence of criminal damages and corporate probation for corporations with the condition to pay compensation to the victim. However, this idea has not been able to work because of Law Number 10 Year 1998 on Amendment to Act Number 7 of 1992 concerning Banking, the corporation is not a subject of criminal law and may be threatened under the Banking Act.Based on the court ruling that always adheres to the principle of legality, the Special Law related to banking crimes that have included corporations as legal subjects, the application of corporate crime in some countries, the concept of the Criminal Code and some research results or studies of banking victims (bank customers), it is necessary to amend the Banking Law by using Strict Liability theory (in the application of Article 46 paragraph (2) for corporations undertaking unauthorized fund raising) and elaborating Vicarious Liability and Identification theory (particularly the application of Articles 49 and 50 A) so as to include some elements, namely 1) adding the subject of corporation law; 2) in the case of the criminal sanction penalapaan maximum penal amount of material damages suffered by the community (bank customers) and seize the property of perpetrators who came from banking crime to be used to compensate victims (bank customers); 3) to extend the scope of criminal subjects which previously only regulates Shareholders, Board of Commissioners, Directors, Employees and Affiliated Parties to include parties involved in banking crime. Key Words: criminal liability, corporation, banking.